Reasons of Demotivation and Perception towards Mathematics - G.C., Laxmi (Educational Journal, 2023)
We have always been motivated as teachers to blame low-performing students by claiming that they have negative attitudes toward mathematics, but we are rarely interested in investigating the reasons for their negative attitudes toward mathematics. The goal of this case study was to look into the reasons why low-performing students have a demotivation attitude toward mathematics. The objective of this case study was to analyze the reasons for having demotivation of mathematics among the low-performing students. A low-performing student in mathematics was selected purposively based on her performance in mathematics as the key research participant from a higher secondary. Low-performing one student in mathematics with the help of her/her previous classroom performances was taken as the sample of the study. The information was gathered through a series of in-depth interviews conducted at various levels. The reasons for having demotivation attitudes of mathematics include: being repeatedly failed in exams, not teacher mediator/learning facilitator, lack of time given for practice, less confidence, and a lack of priori or conceptual knowledge.